Optimized Regulation of Hybrid Adiabatic Compressed Air Energy Storage System for Zero-Carbon-Emission Micro-Energy Network - Jia, Qiwei; Liu, Tingxiang; Chen, Xiaotao; Chen, Laijun; Si, Yang; Mei, Shengwei (Frontiers in Energy Research, 2021)
Improving electricity and heat utilization can speed up China’s decarbonization process in the northwest villages on the Qinghai-Tibet Plateau. In this paper, we proposed an architecture with zero-carbon-emission micro-energy network (ZCE-MEN) to increase the reliability and flexibility of heat and electricity. The advanced adiabatic compressed air energy storage system (AA-CAES) hybrid with solar thermal collector (STC) is defined as hybrid adiabatic compressed air energy storage system (HA-CAES). The ZCE-MEN adopts HA-CAES as the energy hub, which is integrated with power distribution network (PDN) and district heating network (DHN). The STC can greatly improve the efficiency of HA-CAES. Furthermore, it can provide various grades of thermal energy for the residents. The design scheme of HA-CAES firstly considers the thermal dynamics and pressure behavior to assess its heating and power capacities. The optimal operating strategy of ZCE-MEN is modeled as mixed-integer nonlinear programming (MINLP) and converts this problem into a mixed-integer linear programming problem (MILP) that can be solved by CPLEX. The simulation results show that the energy hub based on HA-CAES proposed in this paper can significantly improve ZCE-MEN efficiency and reduce its operation costs. Compared with conventional AA-CAES, the electric to electric (E-E) energy conversion efficiency of the proposed system is increased to 65.61%, and the round trip efficiency of the system is increased to 70.18%. Besides, operating costs have been reduced by 4.78% in comparison with traditional micro-energy network (MEN).